Antiretroviral Therapy Awareness and Risky Sexual Behaviors : Evidence from Mozambique - de Walque, Damien; Kazianga, Harounan; Over, Mead (2012)
This paper studies the effect of increased access to antiretroviral therapy on risky sexual behavior, using data collected in Mozambique in 2007 and 2008. The survey sampled both households of randomly selected HIV positive individuals and households from the general population. Controlling for unobserved individual characteristics, the findings support the hypothesis of disinhibition behaviors, whereby risky sexual behaviors increase in response to the perceived changes in risk associated with increased access to antiretroviral therapy. Furthermore, men and women respond differently to the perceived changes in risk. In particular, risky behaviors increase for men who believe, wrongly, that AIDS can be cured, while risky behaviors increase for women who believe, correctly, that antiretroviral therapy can treat AIDS but cannot cure it. The findings suggest that scaling up access to antiretroviral therapy without prevention programs may not be optimal if the objective is to contain the disease, since people would adjust their sexual behavior in response to the perceived changes in risk. Therefore, prevention programs need to include educational messages about antiretroviral therapy, and address the changing beliefs about HIV in the era of increasing antiretroviral therapy availability.